The national financial adjustment policy and the equalisation of health levels among prefectures. Issue 10 (1st October 2001) - Takano, T; Nakamura, K
Abstract : STUDY OBJECTIVES: The objectives of this study were to examine (1) trends concerning financial assistance from the national government to local governments, (2) trends regarding death rates and life expectancies among prefectures, and (3) the effect of the national financial adjustment policy in equalising both the revenues of local governments and variations in the health levels among prefectures in terms of death rates and life expectancies. DESIGN: The study analysed prefectural income, the amount of national taxes collected, financial assistance from the national government to local governments, and age adjusted death rates and life expectancies of all of the prefectures in Japan during the period from 1965 through 1995. MAIN RESULTS: (1) Under the financial adjustment policy, financial assistance from the national government to the local governments, which consists of the sum of the local allocation tax and treasury disbursements, increased from 1831 billion yen in 1965 to 31 116 billion yen in 1995. (2) During the same period, the age adjusted death rate per 100 000 people decreased from 1168.9 (1965) to 545.3 (1995). The range of variation in the age adjusted death rate among prefectures diminished as the coefficient of variation of the death rate declined from 0.060 in 1965 to 0.043 in 1995. (3) There was a significant statistical correlation between higher prefectural incomes and lower mortality rates during from 1965 until 1975 (p < 0.05), whereas this correlation was indistinct in the 1980s and has not been observed since 1990. (4) The relative health level of Tokyo has declined in terms of its ranking among all the prefectures with regard to life expectancy, from being the best in 1965 to below average in 1995. CONCLUSIONS: The national financial adjustment policy to balance the revenues of local governments has increased the health levels of rural prefectures. It is probable that the policy reduced the disparity in death rates and life expectancies among prefectures throughout the country. However, the policy has precluded the nation's capital city from applying its economic resources as local government expenditures to deal with the megacity issues affecting health.